Gaya Kepemimpinan Transformasional, Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan: Mediasi Motivasi Kerja Pada Pertamina Upstream Data Center (PUDC) - Kumba Digdowiseiso; Nourman Dwi Seftia (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study aims to determine and analyze the effect of transformational leadership, compensation and work discipline on employee performance mediated by work motivation at Pertamina upstream data center (PUDC). The sampling method used is cluster random sampling. From a population of 125, all of them were taken as samples for this study. The analytical method used is Path Analysis using AMOS 22 software. The results of this study show that transformational leadership and compensation have a positive and significant effect on work motivation, work discipline has a negative and significant effect on work motivation, transformational leadership, compensation and work discipline have a positive and significant effect. on employee performance, transformational leadership, compensation and work discipline on employee performance mediated by work motivation has a positive and significant effect.